The Description of Rhabdias globocephala (Nematoda, Rhabdiasidae) from the New Host Buergeria pollicaris (Amphibia, Rhacophoridae) - Kuzmin, Yu.I. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Parasitic nematode Rhabdias globocephala Kung et Wu, 1945 previously known only from the type host, Microhyla ornata from China, is described from a new host, Buergeria pollicaris (Werner, 1914). Differention of the species from closely related R. sphaerocephala Goodey, 1924 is amended based on the shape of anterior cuticular swelling, buccal capsule position, and relative length of oesophagus. The differentiation of R. globocephala from 4 sympatric species of the genus: R. bicornis Lu, 1934, R. bufonis (Schrank, 1788), R. incerta Wilkie, 1930 and R. nipponica Yamaguti, 1935 is also provided.